Apparent Nova in M31: M31N 2010-06c - Pietsch, W.; Henze, M.; Burwitz, V.; Liakos, A.; Hatzidimitriou, D.; Niarchos, P. (Central Bureau Electronic Telegrams, 2010)
Pietsch, Henze, and Burwitz -- together with A. Liakos (Department of Physics, University of Athens), D. Hatzidimitriou (Department of Physics, University of Crete), and P. Niarchos (Department of Physics, University of Athens) -- add that confirmation of M31N 2010-06c at mag 18.0 was obtained with a stack of ten 60-s unfiltered CCD images obtained with a 40-cm Cassegrain telescope (+ f/5.1 focal reducer + 2184x1472-pixel ST-10XME CCD camera; pixel size 6.8 microns square) at the Athens University Observatory on June 27.028 UT; they provide position end figures 04s.48, 33".8.